2021
DOI: 10.1093/mnras/stab1299
|View full text |Cite
|
Sign up to set email alerts
|

Correlated time variability of multicomponent high-velocity outflows in J162122.54+075808.4

Abstract: We present a detailed analysis of time variability of two distinct C iv broad absorption line (BAL) components seen in the spectrum of J162122.54+075808.4 (zem= 2.1394) using observations from SDSS, NTT and SALT taken at seven different epochs spanning about 15 years. The blue-BAL component (with an ejection velocity, ve ∼ 37 500 km s−1) is an emerging absorption that shows equivalent width variations and kinematic shifts consistent with acceleration. The red-BAL component (ve ∼ 15 400 km s−1) is a three compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The requirement of large changes in the ionizing flux can be reconciled if we allow for the C ionizing photon flux to have larger variability compared to what we measure in the FUV range (i.e 𝐹 1640Å ). The scatter can be understood if the C ionizing photon flux has a range of values for a given 𝐹 1640Å (similar discussions in Aromal et al 2021, in the case of J1621+0758). On the other hand, it is also possible that in addition to the changes in the ionizing flux, variations in other parameters such as the covering factor (see discussions in the previous section) or changes in the gas properties could contribute to the scatter.…”
Section: Photometric Variability Of J1322 + 0524mentioning
confidence: 76%
See 4 more Smart Citations
“…The requirement of large changes in the ionizing flux can be reconciled if we allow for the C ionizing photon flux to have larger variability compared to what we measure in the FUV range (i.e 𝐹 1640Å ). The scatter can be understood if the C ionizing photon flux has a range of values for a given 𝐹 1640Å (similar discussions in Aromal et al 2021, in the case of J1621+0758). On the other hand, it is also possible that in addition to the changes in the ionizing flux, variations in other parameters such as the covering factor (see discussions in the previous section) or changes in the gas properties could contribute to the scatter.…”
Section: Photometric Variability Of J1322 + 0524mentioning
confidence: 76%
“…We show the time evolution of the C emission line rest equivalent width obtained from our continuum+Gaussian fits in It is usual procedure to interpret such a correlated variability between different BAL components and BEL equivalent widths to changes in the ionization due to quasar variability (see for example, Aromal et al 2021). Wang et al (2015) have found a correlation between variations in the equivalent widths of C emission lines and BALs in their sample.…”
Section: Correlated Bal Variabilitymentioning
confidence: 92%
See 3 more Smart Citations